Effectiveness of Physical and Psychological Treatment for Cancer-Related Fatigue: Systematic Review - Wulan Syafitry; Dian Hudiyawati (Universitas Muhammadiyah Surakarta, 2021)
Cancer is the second leading cause of death worldwide. Fatigue is one of the most common side effects of people with cancer. The range of people with cancer who experience fatigue is 70-80%, when undergoing cancer treatment and during the phase before and after treatment. This systematic review aims to identify fatigue management with non-pharmacological intervention. The journals selected from 2015 to 2020 in an international database: Pubmed, SAGE journals, Microsoft Academic, and Science Direct. The database searched using the keywords